Comparative phylogeography of three host sea anemones in the Indo‐Pacific - Madeleine A. Emms; Pablo Saenz‐Agudelo; Emily C. Giles; Remy Gatins; Gerrit B. Nanninga; Anna Scott; Jean‐Paul A. Hobbs; Ashley J. Frisch; Suzanne C. Mills; Ricardo Beldade; Michael L. Berumen (Journal of Biogeography, 2020)
Aim The mutualistic relationship between anemones and anemonefishes is one of the most iconic examples of symbiosis. However, while anemonefishes have been extensively studied in terms of genetic connectivity, such information is lacking entirely for host sea anemones. Here, we provide the first information on the broad‐scale population structure and phylogeographical patterns of three species of host sea anemone, Heteractis magnifica, Stichodactyla mertensii and Entacmaea quadricolor . We evaluate if there is concordance in genetic structure across several distinct biogeographical areas within the Indo‐Pacific region and to what extent the observed patterns may concur with those found for anemonefishes. Location Indo‐Pacific, including the Red Sea. Taxon Heteractis magnifica , S. mertensii and E. quadricolor Methods Microsatellite markers and a combination of statistical methods including Bayesian clustering, isolation by distance (IBD), analysis of molecular variance (AMOVA) and principal components analysis (PCA) were used to determine population structure. The congruence among distance matrices (CADM) method was used to assess similarity in spatial genetic patterns among species. Results Significant population structure was identified in the three host anemone species. Each species is likely composed of at least two genetic clusters corresponding to two biogeographical regions, the Red Sea and the rest of the Indo‐Pacific. Two of the three anemone species seem to be experiencing admixture where the two main clusters overlap (the Maldives). IBD analyses in the Red Sea revealed differences in gene flow among species, suggesting more limited dispersal potential for E. quadricolor than for S. mertensii and H. magnifica . Clonality is documented in S. mertensii for the first time. Main conclusions This research documents the genetic population structure for three ecologically important host sea anemones across the Indo‐Pacific and provides valuable insights regarding their biogeography and evolution. Specifically, we found high levels of genetic divergence between populations across different biogeographical regions, suggesting different evolutionary lineages within species. At the same time, common geographical overlap of population structures suggests similar evolutionary histories among all three species. Interestingly, the observed patterns are congruent to some extent with structure reported for several anemonefish species, reflecting their close ecological association.